Diabetes Mellitus Type 5 (Malnutrition-Related Diabetes): Pathophysiology, Clinical Characteristics, and Therapeutic Challenges - Eunike Alicia Valentina; Aryo Hanun Harjanto; Afifah Sekarkusuma; Bernita Nur Cahyani; Maudita Sri Lestari; Kevin Tandarto (GLOBAL HEALTH SCIENCE GROUP, 2026)
Type 5 diabetes mellitus (T5DM), historically referred to as malnutrition-related diabetes mellitus (MRDM), represents an emerging and underrecognized subtype of diabetes that predominantly affects individuals in low- and middle-income countries (LMICs). Unlike type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM), T5DM is characterized by severe insulin deficiency in the absence of autoimmune destruction or significant insulin resistance, reflecting a distinct pathophysiological mechanism linked to chronic undernutrition and impaired pancreatic development. Despite increasing recognition, variability in terminology, diagnostic criteria, and clinical characterization has limited its identification and management in both clinical practice and research settings. This narrative literature review aims to synthesize current evidence on the epidemiology, pathophysiology, clinical features, and therapeutic approaches of T5DM, as well as to evaluate its distinction from classical diabetes subtypes and its implications for global health. A structured literature search was conducted across major electronic databases, including PubMed, Scopus, EMBASE, and Google Scholar, covering publications from January 2020 to March 2026. Relevant studies were selected based on predefined inclusion criteria encompassing epidemiological data, mechanistic insights, clinical characteristics, and treatment outcomes. Due to heterogeneity in study design, populations, and reported outcomes, findings were synthesized descriptively. The available evidence indicates that T5DM typically presents in young, underweight individuals with preserved insulin sensitivity, detectable but reduced C-peptide levels, and minimal risk of ketosis despite significant hyperglycemia. Pathophysiological mechanisms involve early-life nutritional deprivation leading to reduced β-cell mass, epigenetic modifications, and impaired insulin secretion. Therapeutically, patients often require lower insulin doses and may respond to selected oral antidiabetic agents, although evidence remains limited. Significant diagnostic challenges persist, particularly in resource-limited settings, where misclassification as T1DM or T2DM is common.